Cerebral Salt Wasting Syndrome in Traumatic Epidural Hematoma and Subarachnoid Hemorrhage: A Case Report - Chandrika Najwa Malufti; Stephanus Andy Prakasa Kaligis; Harris Istianggoro; Kathi Swaputri Kancana (Universitas Airlangga, 2023)
Highlight: CSWS is a rare case of hyponatremia in central nervous system disorders. The correct diagnosis of CSWS is very important because it has a different treatment strategy from other diseases so that patients will get a good outcome. ABSTRACT Introduction: Electrolyte imbalance is common in patients with neurologic disease, including traumatic brain injury. The most common type is hyponatremia, a condition in which serum sodium <135 mmol/L. High morbidity and mortality rates are associated with hyponatremia, especially if the underlying causes are misdiagnosed and improperly treated. One such condition that comes to mind is cerebral salt wasting syndrome (CSWS), which is treated primarily with volume resuscitation and sodium replacements and is characterized by hyponatremia, elevated urine sodium, and hypovolemia. Case: A 21-year-old man was hospitalized for a traumatic brain injury due to a traffic accident. He suffered from an epidural hematoma (EDH) and a subarachnoid hemorrhage (SAH). He underwent an emergency decompression craniotomy and hematoma evacuation. The operation went well, as expected. During hospitalization, the patient developed agitation, restlessness, and polyuria with hyponatremia in serum but elevated in urine. We identified that CSWS was the underlying cause and administered isotonic, hypertonic, and hydrocortisone treatments to the patient. The patient showed progressive improvement. His condition tends to be stable, and he has a normal electrolyte level. Conclusion: Cerebral salt wasting syndrome (CSWS) is an important but underrecognized cause in hyponatremic patients with central nervous system disorders.